Comparative Analysis Study of Audit Quality in Indonesia and Global - Kumalawati, Lely; Wibawa, Koerniawan Dwi (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Introduction/Main Objectives: This study applies the Krippendorff method, which aims to analyze the characteristics, themes, and concepts of audit quality research conducted by Indonesian and global researchers. Background Problems: Audit quality is a measurement often used to assess auditor performance. Novelty: This study identified articles with the keyword